Implementasi Layanan Akademik Berbasis Chatbot untuk Meningkatkan Interaksi Mahasiswa - Akhyar Lubis; Isnar Sumartono (STMIK Budi Darma, 2023)
Information and communication technology advancement has transformed the landscape of education in various academic institutions. To address the increasingly complex demands faced by students, universities need to adopt innovations to enhance the quality of services and interactions with students. One promising innovation is the use of chatbots in the context of academic services. A chatbot is an artificial intelligence-based application capable of interacting with users through a conversational interface. In this study, the implementation of a chatbot-based academic service is proposed to enhance student interactions at Panca Budi University. The needs analysis results indicate that students require direct and real-time access to interact with the educational service system. In the design of the chatbot architecture, several services in AWS, such as AWS Lambda, Amazon Lex, Amazon DynamoDB, Amazon API Gateway, Amazon CloudFront, and Amazon S3, are utilized. The implementation of the chatbot is performed through configuration in Amazon Lex and integration with Twilio. The results of the performance of the chatbot-based academic service can improve student interactions by providing quick and easy access to information.